2017
DOI: 10.1002/adhm.201600914
|View full text |Cite
|
Sign up to set email alerts
|

Cell Guidance on Nanostructured Metal Based Surfaces

Abstract: Metal surface nanostructuring to guide cell behavior is an attractive strategy to improve parts of medical implants, lab-on-a-chip, soft robotics, self-assembled microdevices, and bionic devices. Here, we discus important parameters, relevant trends, and specific examples of metal surface nanostructuring to guide cell behavior on metal-based hybrid surfaces. Surface nanostructuring allows precise control of cell morphology, adhesion, internal organization, and function. Pre-organized metal nanostructuring and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 130 publications
(189 reference statements)
0
24
0
Order By: Relevance
“…[52] The latter development of micro-and nanofabrication techniques led to an increase in experimental setups using micro-and nanopatterns for in vitro studies. [53][54][55] The cellular response to the surface nanotopography and its correlation to the surface-bound proteins have been highlighted by Lim et al who showed that cell adhesion was unaffected by surface nanotopography if performed in the absence of serum. [56] This was a very important finding which allowed speculations that implant surfaces should be designed not for cells but more prominently for proteins as primary targets.…”
Section: Protein Adsorption Guided By Surface Physicochemical Factorsmentioning
confidence: 99%
“…[52] The latter development of micro-and nanofabrication techniques led to an increase in experimental setups using micro-and nanopatterns for in vitro studies. [53][54][55] The cellular response to the surface nanotopography and its correlation to the surface-bound proteins have been highlighted by Lim et al who showed that cell adhesion was unaffected by surface nanotopography if performed in the absence of serum. [56] This was a very important finding which allowed speculations that implant surfaces should be designed not for cells but more prominently for proteins as primary targets.…”
Section: Protein Adsorption Guided By Surface Physicochemical Factorsmentioning
confidence: 99%
“…Besides their chemical properties, others have already proposed that the material surface topography is fundamental for this process. [8] Recently, we have shown the prospects of nanostructured titania surfaces for the development of lab-on-a-chip, light-triggered systems to guide proteins on the cell surface by dynamic oscillation of soft matter organized on titania to regulate inorganic-organic-polymeric interfaces. [9][10][11] Several studies using surface structuring approaches demonstrate that cells respond to nanotopography.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium is a common material used in dental and orthopaedic implants due to its inertness and high mechanical strength. [8] It is easy to integrate as an element of light-sensitive systems due to photoactivity of the titania layer. [19] A variety of surface modification strategies can be employed to titaniumbased implants to enhance osseointegration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations